James and the giant peach - Dahl, Roald; Blake, Quentin (London : Puffin Books, 1995)
A young boy escapes from two wicked aunts and embarks on a series of adventures with six large insects he meets inside a giant peach.
"The original story illustrated in full color by Quentin Blake"--Cover.
4.8
3-6.
3-6
Keywords: Aunts -- Juvenile fiction; Fairy tales; Insects -- Juvenile fiction; Peach -- Juvenile fiction; Aunts -- Fiction; Fairy tales; Fantasy; Insects -- Fiction; Peach -- Fiction; Aunts -- Fiction; Fairy tales; Insects -- Fiction; Peach -- Fiction; Fantastic fiction; Fantastic fiction; Fairy tales